Enhancing VTA Ca(v)1.3 L-type Ca(2+) channel activity promotes cocaine and mood - related behaviors via overlapping AMPA receptor mechanisms in the nucleus accumbens - Martínez-Rivera, Arlene (Mol Psychiatry, 2017)
Genetic factors significantly influence susceptibility for substance abuse and mood disorders. Rodent studies have begun to elucidate a role of Ca(v)1.3 L-type Ca(2+) channels in neuropsychiatric-related behaviors, such as addictive and depressive-like behaviors. Human studies have also linked the CACNA1D gene, which codes for the Ca(v)1.3 protein, with bipolar disorder (BD). However, the neurocircuitry and the molecular mechanisms underlying the role of Ca(v)1.3 in neuropsychiatric phenotypes are not well established. In the present study, we directly manipulated Ca(v)1.3 channels in Ca(v)1.2 dihydropyridine (DHP) insensitive mutant mice and found that VTA Ca(v)1.3 channels mediate cocaine-related and depressive-like behavior through a common nucleus accumbens (NAc) shell calcium permeable AMPA receptor (CP-AMPAR) mechanism that requires GluA1 phosphorylation at S831. Selective activation of VTA Ca(v)1.3 with (±)-BayK-8644 (BayK) enhanced cocaine conditioned place preference (CPP) and cocaine psychomotor activity while inducing depressive-like behavior, an effect not observed in S831A phospho-mutant mice. Infusion of the CP-AMPAR-specific blocker Naspm into the NAc shell reversed the cocaine and depressive-like phenotypes. In addition, activation of VTA Ca(v)1.3 channels resulted in social behavioral deficits. In contrast to the cocaine- and depression-related phenotypes, GluA1/A2 AMPARs in the NAc core mediated social deficits, independent of S831-GluA1 phosphorylation. Using a candidate gene analysis approach, we also identified single nucleotide polymorphisms in the CACNA1D gene associated with cocaine dependence (CD) in human subjects. Together, our findings reveal novel, overlapping mechanisms through which VTA Ca(v)1.3 mediates cocaine-related, depressive-like and social phenotypes suggesting that Ca(v)1.3 may serve as a target for the treatment of neuropsychiatric symptoms.